2022
DOI: 10.1111/iar.12458
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of the Paleo‐Kuril arc inferred from detrital zircon U–Pb chronology in eastern Hokkaido, NE Asia

Abstract: The Nemuro and Saroma Groups and Yusenkyo Formation occur in eastern Hokkaido and are considered to be forearc or intra‐arc basin sediments of the Paleo‐Kuril arc (PKA) deposited during the Late Cretaceous to middle Eocene. To further clarify the origin of the PKA, we examined the U–Pb ages of detrital zircons within these sandstones and acidic tuff beds; based on our results, we drew the following conclusions. (1) The PKA originated from an oceanic island arc on the oceanic Izanagi Plate around 85 Ma, to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 75 publications
(227 reference statements)
0
11
0
Order By: Relevance
“…The sample of the Lowest Saroma Group measured by Nanayama et al 7 indicated intermediate Bayesian Population Correlations values (0.06–0.58) with Type 1 distributions (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The sample of the Lowest Saroma Group measured by Nanayama et al 7 indicated intermediate Bayesian Population Correlations values (0.06–0.58) with Type 1 distributions (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 83%
“…While in the Tokoro Belt, radiometric and biostratigraphic ages were analyzed, such as: Dinoflagellate 30 , Radiolarians 31 , 32 , and K–Ar dating 33 . Detrital zircon U–Pb analysis from Harisma et al 6 ( a – g , k , l , o ); Nanayama et al 7 ( h , i , m , n , u ). n number of zircon grain analyses, Fm formation, Mbr member.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations